Electromagnetic radiation of human body before and after intense exercise - R.S.S.A. Kadir; Zunairah Hj Murat; Nizaar Suhairy Bin Johari (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper investigates the electromagnetic radiation (EMR) of the human body before and after intense exercise. The intensity of exercise refers to the rate or the effort at which the activity is being performed. 30 healthy students participated in this research. The data were collected at the specific point of the human body by using a frequency detector. The reading of the frequency was taken 5 times at each point at the same location; hence, the average value is calculated for data analysis. This frequency measurement is recorded two times which is before and after intense exercise with a consistence protocol for all participants. The collected data is analyzed by using MATLAB programming tool which converts the data frequency into 15 colours of bio-energies which symbolizes different energy field score. The score represents the health level of the samples at specific point. From the analysis, higher frequency of EMR is detected after intense exercise compared to before intense exercise. There is also a significant change in the physical health score categories. This indicates that the intense exercise influences the body EMR radiation frequencies.